2021
DOI: 10.1177/0956797620977516
|View full text |Cite
|
Sign up to set email alerts
|

Encoding Context Determines Risky Choice

Abstract: Both memory and choice are influenced by context: Memory is enhanced when encoding and retrieval contexts match, and choice is swayed by available options. Here, we assessed how context influences risky choice in an experience-based task in two main experiments (119 and 98 participants retained, respectively) and two additional experiments reported in the Supplemental Material available online (152 and 106 participants retained, respectively). Within a single session, we created two separate contexts by presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The model can also explain why options that were locally optimal in small magnitude contexts might be preferred over options that were locally suboptimal in large magnitude contexts, even if the latter have a higher objective value . Finally, the RANGE model's assumption that decision makers track the minimum and maximum rewards in each context is consistent with the finding of enhanced memory for the most extreme outcomes in experience-based decision tasks (Madan et al, 2014(Madan et al, , 2021.…”
Section: Range Adaptationsupporting
confidence: 71%
See 1 more Smart Citation
“…The model can also explain why options that were locally optimal in small magnitude contexts might be preferred over options that were locally suboptimal in large magnitude contexts, even if the latter have a higher objective value . Finally, the RANGE model's assumption that decision makers track the minimum and maximum rewards in each context is consistent with the finding of enhanced memory for the most extreme outcomes in experience-based decision tasks (Madan et al, 2014(Madan et al, , 2021.…”
Section: Range Adaptationsupporting
confidence: 71%
“…In contrast, the mean estimates of the highest and lowest outcomes in each context matched the structure of the task, even though the estimates significantly deviated from the actual values. This may be due to enhanced memory for outcomes at or near the edge of the contextual distribution (Madan et al, 2014(Madan et al, , 2021. Full ANOVA results for the estimation data can be found in Supplemental Note 3.…”
Section: Figurementioning
confidence: 99%
“…Even though participants may have tried to retrieve previous outcomes from long-term memory when novel choice pairs were encountered in the transfer test, that information may have been unavailable for some because it was never encoded in the first place. Supporting this interpretation, others have shown that context-dependent preferences in experience-based choice are rooted in contextual comparisons that happen at the time of encoding, rather than at the time of retrieval (Madan et al, 2021).…”
Section: Methodsmentioning
confidence: 97%
“…When rewards differ in magnitude, risky choice depends on the set of outcomes in the decision context (see Madan et al, 2021). When monetary outcomes are learned through experience, people often show context-dependent biases in which they are more risk seeking for choices involving the best outcomes in the context (e.g., gains or high-value rewards) than for choices involving losses or lower value rewards (e.g., Konstantinidis et al, 2018; Ludvig et al, 2014).…”
mentioning
confidence: 99%